2012
DOI: 10.1371/journal.pone.0042989
|View full text |Cite
|
Sign up to set email alerts
|

Withaferin-A Reduces Type I Collagen Expression In Vitro and Inhibits Development of Myocardial Fibrosis In Vivo

Abstract: Type I collagen is the most abundant protein in the human body. Its excessive synthesis results in fibrosis of various organs. Fibrosis is a major medical problem without an existing cure. Excessive synthesis of type I collagen in fibrosis is primarily due to stabilization of collagen mRNAs. We recently reported that intermediate filaments composed of vimentin regulate collagen synthesis by stabilizing collagen mRNAs. Vimentin is a primary target of Withaferin-A (WF-A). Therefore, we hypothesized that WF-A may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…While peak plasma concentration of WA after dietary exposure has not been assessed, Thaiparambil et al showed that peak plasma concentration of WA following 4 mg/kg ( i.p ) was 2 μM [54]. In addition to the well-established therapeutic and preventive role of WA in cancer, it has also been shown to have therapeutic effects against hepatotoxicity [55] [56], diabetes [57] and cardiac fibrosis [58]. Results from our hepatotoxicity experiments are in line with the protective and therapeutic phenotypes exhibited by WA in other models.…”
Section: Discussionmentioning
confidence: 99%
“…While peak plasma concentration of WA after dietary exposure has not been assessed, Thaiparambil et al showed that peak plasma concentration of WA following 4 mg/kg ( i.p ) was 2 μM [54]. In addition to the well-established therapeutic and preventive role of WA in cancer, it has also been shown to have therapeutic effects against hepatotoxicity [55] [56], diabetes [57] and cardiac fibrosis [58]. Results from our hepatotoxicity experiments are in line with the protective and therapeutic phenotypes exhibited by WA in other models.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that mRNAs may also associate with intermediate filaments, as ultrastructural in situ hybridization experiments disclosed that about 29% of total poly(A) + mRNAs are found close to or associated with vimentin filaments (Bassell et al, 1994). Challa and colleagues showed that vimentin filaments modulate post-transcriptional gene expression by association and stabilization of collagen mRNAs and thereby may play a role in development of tissue fibrosis (Challa and Stefanovic, 2011;Challa et al, 2012). It was also reported that vimentin interacts with the 5′-untranslated region of the mouse mu opoid receptor mRNA and serves as a post-transcriptional negative regulator of gene expression (Song et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting fibrosis may prevent progression of disease and be a complementary therapeutic for regeneration. For example, administration of withaferin-A, which binds and inhibits vimentin, reduced collagen mRNA half-life, collagen protein production, transcription of collagen genes, and interstitial fibrosis (59). Because engineered cardiac tissue will likely be delivered to a fibrotic environment, we must consider the role of fibroblasts when used as a cell source for tissue engineering (e.g., as a support cell for ECM maintenance) and take into account the host fibroblast and myofibroblast populations, which may act as barriers to or facilitators of integration of implanted engineered tissue.…”
Section: Stem Cells and Cell Sourcingmentioning
confidence: 99%